IMPLEMENTASI SISTEM MANAJEMEN UMKM RUMAH MAKAN LAMONGAN TERINTEGRASI BERBASIS WEB DAN ANDROID - Laurentinus Laurentinus; Fransiskus Panca Juniawan (Informatics Engineering Department of Halu Oleo University, 2018)
Nowadays, we can find Lamongan Restaurants wherever we are. Almost every street there is one Lamongan Restaurant. One of these types of UMKM is so popular among the public. This happened because the food that offered was acceptable and became a favorite for the public, as well as what happened in Bangka Belitung Province. However, most UMKM still uses manual methods for bookkeeping and transactions. Problems arise when many customers come to place to order, as well as those who want to make payments must wait for the manual calculation. Besides, manual bookkeeping can still cause errors in the calculation. To solve this problem, an integrated management system is proposed throughout the Province of Bangka Belitung. That way, every UMKM can easily do bookkeeping and transactions, besides that the government can also easily to monitor, record, and access the information reports from UMKM. This study uses a prototype development model. The results are the implementation of the integrated management system for Lamongan Restaurants in Bangka Belitung province based on the web and Android.Keywords—Management Information System, Integration, UMKM Lamongan Restaurant, Android, Web ServerDOI: 10.5281/zenodo.2010359